2017
DOI: 10.1124/mol.116.107755
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Preclinical Studies of Computationally Designed Non-Nucleoside Reverse Transcriptase Inhibitors for Treating HIV infection

Abstract: The clinical benefits of HIV-1 non-nucleoside reverse transcriptase (RT) inhibitors (NNRTIs) are hindered by their unsatisfactory pharmacokinetic (PK) properties along with the rapid development of drug-resistant variants. However, the clinical efficacy of these inhibitors can be improved by developing compounds with enhanced pharmacological profiles and heightened antiviral activity. We used computational and structure-guided design to develop two next-generation NNRTI drug candidates, compounds I and II, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…To date, there are no structural data available for (−)/(+)FTC‐TP and (−)3TC‐TP in complex with RT. The recent success in structure‐based design of novel nonnucleoside reverse transcriptase inhibitors (NNRTIs) with improved pharmacokinetics and less susceptibility toward drug resistance underscore the value of structural data . Similarly, in order to understand the molecular basis of recognition for NRTIs by RT and host Pols important in toxicity, obtaining structural data of RT in complex with (−)FTC‐TP and (−)3TC‐TP is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there are no structural data available for (−)/(+)FTC‐TP and (−)3TC‐TP in complex with RT. The recent success in structure‐based design of novel nonnucleoside reverse transcriptase inhibitors (NNRTIs) with improved pharmacokinetics and less susceptibility toward drug resistance underscore the value of structural data . Similarly, in order to understand the molecular basis of recognition for NRTIs by RT and host Pols important in toxicity, obtaining structural data of RT in complex with (−)FTC‐TP and (−)3TC‐TP is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Lower plasma clearance than EFV also suggested that the catechol derivative had improved metabolic stability. In addition, no acute toxic effects were observed after the administration of a higher dose of 100 mg/kg over a period of 96 hours . In a humanized mouse model of HIV‐1 infection, compound 120 significantly reduced the viral load and prevented the loss of human CD4 + T cells following a 100 mg/kg daily dose regime .…”
Section: Drug Design Strategiesmentioning
confidence: 98%
“…In addition, no acute toxic effects were observed after the administration of a higher dose of 100 mg/kg over a period of 96 hours. 138 In a humanized mouse model of HIV-1 infection, compound 120 significantly reduced the viral load and prevented the loss of human CD4 + T cells following a 100 mg/kg daily dose regime. 139 Furthermore, a long-acting nanoformulation of the compound was developed, which was able to maintain therapeutic plasma concentration and anti-HIV activity for almost 3 weeks after a single dose, and synergic effect of the catechol was demonstrated with different NRTIs and integrase inhibitors in cell-based assays.…”
Section: Computer-aided Optimizationmentioning
confidence: 98%
See 2 more Smart Citations